Transcriptome analysis for the chicken based on 19,626 finished cDNA sequences and 485,337 expressed sequence tags - Hubbard, Simon J.; Grafham, Darren V.; Beattie, Kevin J.; Overton, Ian M.; McLaren, Stuart R.; Croning, Michael D.R.; Boardman, Paul E.; Bonfield, James K.; Burnside, Joan; Davies, Robert M.; Farrell, Elizabeth R.; Francis, Matthew D.; et al. (Genome Research, 2005)
We present an analysis of the chicken (Gallus gallus) transcriptome based on the full insert sequences for 19,626 cDNAs, combined with 485,337 EST sequences. The cDNA data set has been functionally annotated and describes a minimum of 11,929 chicken coding genes, including the sequence for 2260 full-length cDNAs together with a collection of noncoding (nc) cDNAs that have been stringently filtered to remove untranslated regions of coding mRNAs. The combined collection of cDNAs and ESTs describe 62,546 clustered transcripts and provide transcriptional evidence for a total of 18,989 chicken genes, including 88% of the annotated Ensembl gene set. Analysis of the ncRNAs reveals a set that is highly conserved in chickens and mammals, including sequences for 14 pri-miRNAs encoding 23 different miRNAs. The data sets described here provide a transcriptome toolkit linked to physical clones for bioinformaticians and experimental biologists who wish to use chicken systems as a low-cost, accessible alternative to mammals for the analysis of vertebrate development, immunology, and cell biology.